Preserving the gotong royong character for Indonesian Gen-Z in the digital era - Muhamad Murtadlo; Hasan Albana; Muhammad Irfan Helmy; Yuyun Libriyanti; Nurul Qolbi Izazy; Gazi Saloom (International Journal of Evaluation and Research in Education (IJERE), 2024)
Gotong royong is a significant character for Indonesian generation Z (Gen-Z), based on traditional values, to unite this multicultural nation. However, the rapid development of digital media has the potential to alter traditional values. Gen-Z has the ability to quickly adapt to this technology. However, there is a concern that the gotong royong character may decline with the rise of digital media. This research investigates the perception of Gen-Z towards the gotong royong character and explores the way to preserve this value. This is qualitative descriptive research, whose population is made up of 108 students from six excellent schools in three Indonesian cities with different religious backgrounds and educational systems. The results show that Gen-Z still considers the gotong royong value is important. However, they also acknowledge that it can be threatened by the advancement of digital technology. With this awareness, Gen-Z can explore ways to adopt digital technology to preserve this character value, such as utilizing digital learning in club study and digital fundraising. This research recommends optimizing the school institution to take a more active role in fostering character through online character-building learning.